Microfluidics: Simultaneous or Sequential Orthogonal Gradient Formation in a 3D Cell Culture Microfluidic Platform (Small 5/2016). Issue 5 (1st February 2016) - Uzel, Sebastien G. M.; Amadi, Ovid C.; Pearl, Taylor M.; Lee, Richard T.; So, Peter T. C.; Kamm, Roger D.
Abstract : The microfluidic designed by R. D. Kamm and co‐workers allow the formation of simultaneous or sequential concentration gradients within a 3D extracellular matrix. On page 612, these gradients can be used to investigate biological phenomena, such as the differentiation of progenitor cells into neurons as it occurs within the developing spinal cord, or the dynamics of chemotaxis when cells are exposed to time‐dependent concentration profiles.